School in pioneer times - Graves, Kerry A (North Mankato, Minnesota : Capstone Press, [2017])
"Discusses the school life of children in pioneer times, including lessons, books, teachers, examinations and special days"--
A gift from book Africa
Education
1 2 13
NEW_ZTN_GN
Keywords: Education -- United States -- History -- 19th century -- Juvenile literature; Frontier and pioneer life -- United States -- Juvenile literature; Schools -- United States -- History -- 19th century -- Juvenile literature